Estimation of the presence of small dense lipoprotein cholesterol in acute ischemic stroke - Yasuhiro Manabe; Ryuta Morihara; Kosuke Matsuzono; Yumiko Nakano; Yoshiaki Takahashi; Hisashi Narai; Nobuhiko Omori; Koji Abe (MDPI AG, 2015)
Small dense low-density lipoprotein (sdLDL) is an established risk factor in ischemic heart disease. However, its clinical significance in acute ischemic stroke (AIS) is uncertain. This study evaluates the prognostic value of the presence of sdLDL in patients with AIS by determining whether it contributes to clinical outcome or not. We studied 530 consecutive patients admitted within the first 48 hours after onset of ischemic stroke and 50 corresponding controls. Serum lipid parameters were measured on admission by standard laboratory methods. The percentage of AIS patients with sdLDL was significantly higher than the one of matched controls with sdLDL. Concerning comparisons between AIS patients with or without sdLDL, the percentages of males and patients with histories of smoking, hypertension, and cardiovascular disease were significantly higher in AIS patients with sdLDL. Concerning the grade of severity, modified Rankin Scale (mRS) on discharge was significantly higher in AIS patients with sdLDL. On logistic regression analysis, age (OR=2.29, P3). Our study showed that the presence of sdLDL might be independently associated with a poor prognosis after AIS.